2010
DOI: 10.1111/j.1651-2227.2010.01770.x
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare service use in adolescents with non‐specific musculoskeletal pain

Abstract: Non-specific musculoskeletal pain is a frequent event in Italian adolescents and that a large number of these subjects consult a healthcare service.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
27
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 25 publications
6
27
1
Order By: Relevance
“…A study from Italy found that 96.8% of adolescents with non-specific musculoskeletal pain were advised to rest and use medication, seek physical therapy and rehabilitation, or a combination of these [29]. However they also found that only 70% of the adolescents complied with the advice.…”
Section: Discussionmentioning
confidence: 99%
“…A study from Italy found that 96.8% of adolescents with non-specific musculoskeletal pain were advised to rest and use medication, seek physical therapy and rehabilitation, or a combination of these [29]. However they also found that only 70% of the adolescents complied with the advice.…”
Section: Discussionmentioning
confidence: 99%
“…Our overall estimate that 1 in 8 children made physician visits each year for MSD is considerably higher than previous estimates. However, previous studies tend to base their estimates on a limited age range of patients with MSD, mainly adolescents [9,10], data from only one sector of the healthcare system, such as primary care [11], or a restricted range of diagnostic terms [11,12]. To our knowledge, this is the first study to describe the prevalence of healthcare utilization over the full age range of the paediatric population using an inclusive definition of musculoskeletal disorders and all types of physicians for a large and representative population.…”
Section: Discussionmentioning
confidence: 99%
“…20 Epidemiological studies have reported increased rates of health services use by children with chronic pain in Europe and Asia. 19, 26, 37 For example, Perquin et al (2000) found high rates of physician consultation (57%) and medication use (39%) in a community sample of children with chronic pain in the Netherlands. 26 Small single-site investigations have also reported on high rates of physician consultation.…”
Section: Introductionmentioning
confidence: 99%